Can native shrubs facilitate the early establishment of contrasted co‐occurring oaks in Mediterranean grazed areas?. (7th July 2017) - Costa, A.; Villa, S.; Alonso, P.; García‐Rodríguez, J.A.; Martín, F.J.; Martínez‐Ruiz, C.; Fernández‐Santos, B.
Abstract: Questions: Can shrubs ( Cytisus multiflorus ) and large herbivore exclusion (fence) facilitate seedling survival and growth of marcescent and sclerophyllous oaks ( Quercus pyrenaica vs Q. ilex subsp. ballota ) under a bioclimatic limit in Mediterranean grazed areas? Location: Open oak woodlands, central‐western Spain. Methods: A 2‐yr field experiment was conducted by planting 200 seedlings of each Quercus species under four different treatments combining the influence of nurse shrubs and fencing on Quercus seedling survival and growth. Results: Cytisus multiflorus enhanced poor Quercus seedling survival found in the study area, at least during the first 2 yr after planting and particularly during the first dry season. The improvement in soil organic matter under the shrub canopy may have contributed to this positive effect, which was more pronounced on Q. pyrenaica seedlings. Seedling herbivory did not seem to be a limitation to survival. Increased seedling growth in both species was also very low, and no growth was recorded 2 yr after planting without shrubs. The positive shrub effect on seedling growth, especially marked in fenced areas, was more important in Q. pyrenaica in the first growing period and in Q. ilex in the second; 2 yr after planting no difference in shrub effect on growth was found in either Quercus species. Seedling herbivory was a limitation to seedling growth in areas without shrubs, mainly in the case of Q. pyrenaica . Conclusions: In Mediterranean grazed areas with important summer drought and very sandy soil, shrubby C. multiflorus plants have a clear facilitative effect on seedlings of ecologically contrasted Quercus species. The facilitative effect was found in both marcescent and sclerophyllous oak seedlings, but to a different degree depending on the species considered and the variable measured (survival or growth). In terms of survival, the marcescent species was more favoured by shrub cover than the sclerophyllous one, and this effect was accentuated through time. However, in terms of growth, although Q. pyrenaica was initially more favoured by shrubs, differences between the two species were attenuated after 2 yr. Therefore, C. multiflorus can have a key role in restoration of these oak degraded environments. Abstract : In Mediterranean grazed areas with important summer drougth and very sandy soils, Cytisus multiflorus have a clear facilitative effect on marcescent and sclerophyllous oak seedlings, but to a different degree depending on the species considered and the variable measured (survival or growth). Therefore, C. multiflorus can have a key role in the restoration of these oak degraded environments.